Efektivitas Latihan Senam Kebugaran Jasmani 2018 Terhadap Peningkatan Kesegaran Jasmani - Muhammad Rusli; Suhartiwi Suhartiwi; Marsuna Marsuna (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
The purpose of this study was to determine the effectiveness of the 2018 physical fitness exercise on increasing physical fitness. This type of research uses experimental research. The population in this study were all female students of class XI SMA Negeri 24 Konawe Selatan, amounting to 44 people, while the sampling technique used a total sampling technique, namely all female students, amounting to 44 people. The instrument in this study was a physical fitness test for Indonesian children aged 16-19 years consisting of 5 items, namely: 1) sprinting 60 meters, 2) hanging elbow bending test for 60 seconds, 3) lying down for 60 seconds, 4) jumping upright and 5 ) run 1000 meters. The results of the analysis show that there is a significant effectiveness of exercise with physical fitness in 2018 to increase physical fitness, namely before doing physical fitness exercises by 12.89 and after exercising physical fitness by 16.02.